2021
DOI: 10.2196/29682
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Diagnosis of Diminutive Colorectal Polyps in Endoscopic Images: Systematic Review and Meta-analysis of Diagnostic Test Accuracy

Abstract: Background Most colorectal polyps are diminutive and benign, especially those in the rectosigmoid colon, and the resection of these polyps is not cost-effective. Advancements in image-enhanced endoscopy have improved the optical prediction of colorectal polyp histology. However, subjective interpretability and inter- and intraobserver variability prohibits widespread implementation. The number of studies on computer-aided diagnosis (CAD) is increasing; however, their small sample sizes limit statis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Modeling is an assumption that observations follow certain statistical rules, and external validation is a method to check whether this assumption is correct or generalizable. Therefore, the confirmation of performance in the established CAD models with unused data in the training or internal testing process is essential [53]. However, no single study conducted performance verification in an external validation setting.…”
Section: Limitationsmentioning
confidence: 99%
“…Modeling is an assumption that observations follow certain statistical rules, and external validation is a method to check whether this assumption is correct or generalizable. Therefore, the confirmation of performance in the established CAD models with unused data in the training or internal testing process is essential [53]. However, no single study conducted performance verification in an external validation setting.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, artificial intelligence has been introduced to the field of colonoscopy to address the suboptimal performance of human-based optical diagnosis. Several studies have suggested that computer-aided diagnosis (CADx) can help increase the high confidence rate and accuracy regardless of the endoscopist's prior knowledge [3,17]. However, according to ex vivo studies, CADx faces the same challenge of poor translation to real-time optical diagnosis.…”
Section: Baselinementioning
confidence: 99%
“…Use of the 3second rule resulted in significant improvement especially among nonexpert endoscopists. Many studies have achieved exceptional performances in ex vivo optical diagnosis with CADx, but translation into real-time optical diagnosis has been challenging [17]. Implementing a 3-second rule in real-time optical diagnosis would be useful for nonexpert endoscopists to help differentiate between high confidence and low confidence decisions in optical diagnosis.…”
Section: Baselinementioning
confidence: 99%
“…For example, the use of artificial intelligence in endoscopic assessment of inflammatory bowel disease will minimize the need to obtain colonic biopsies and subsequent pathological assessment [61]. It will also help to identify diminutive nonneoplastic polyps that would otherwise be removed and require pathological assessment [62,63]. In a recent study, artificial intelligence was estimated to reduce the average colonoscopy cost and the gross annual reimbursement for colonoscopies by up to 18.9% and US$149.2 million, respectively, in different countries [64].…”
Section: Challenges Associated With Artificial Intelligencementioning
confidence: 99%